Handbook of research on human factors in contemporary workforce development - Christiansen, Bryan 1960-; Chandan, Harish C. 1947- (Advances in human resources management and organizational development (AHRMOD) book series, 2017)
"The development of any organization is deeply connected with the influences of its employees. By implementing new competencies in the workforce, both the employees and the business overall can thrive. [This book] is a pivotal source for the latest scholarly perspectives on social aspects and employee influences on modern business environments. Including a range of topics such as gender diversity, performance appraisal, and job satisfaction, this publication is an ideal reference for academics, professionals, students, and practitioners seeking content on optimizing development in contemporary organizations" - Provided by publisher